Marked respiratory-related fluctuations in left ventricular outflow tract gradients in hypertrophic obstructive cardiomyopathy: an observational study. (7th September 2017) - Jain, Renuka; Osranek, Martin; Jan, M Fuad; Kalvin, Lindsey R; Olet, Susan; Allaqaband, Suhail Q; Jahangir, Arshad; Khandheria, Bijoy K; Tajik, A Jamil
Abstract: Aims: Left ventricular outflow (LVOT) obstruction in patients with hypertrophic cardiomyopathy (HCM) is dynamic and sensitive to many variables that affect left ventricular preload, afterload, and contractility. The haemodynamic effect of normal respiration on LVOT obstruction has not been described. Methods and results: We examined 20 patients with HCM who were noted to have phasic respiratory variation of LVOT obstruction on initial transthoracic 2D echocardiogram and Doppler examination. LVOT gradients were re-examined with simultaneous recording of a respirometer. LVOT gradients varied widely during the respiratory cycle; peak gradients were uniformly lowest during inspiration (50.8 mmHg + 25.6) and highest during expiration (90.1 mmHg + 41.8). On average, there was 82.4% ± 39.1 ( P  ≤ 0.0001) incremental change from inspiration to expiration, in the severity of LVOT obstruction. In 11 patients with mitral annulus inflow, LV inflow (preload) was decreased during inspiration. In 16 patients with isovolumic relaxation time and ejection time measurements, decreased left atrial filling pressure was noted during inspiration, consistent with decreased LVOT obstruction. When compared with a control group of 20 HCM patients who did not have respiratory variation, the study group patients were more overweight (mean body mass index cases 35.1 ± 7.3 vs. control group 29.1 ± 5.1, P  = 0.0045) and more likely to have sleep-disordered breathing ( n  = 15 study group, n  = 5 control group). Conclusions: Counterintuitive respiratory-related fluctuations in LVOT gradients were observed in this case series of 20 HCM patients. These findings challenge traditional haemodynamic teaching and demonstrate the contribution of LV transmural pressure to LVOT obstruction in certain HCM patients.